Pengaruh Pengetahuan, Sosialisasi, Insentif Pajak dan Kepercayaan Otoritas Pajak Terhadap Kepatuhan PBB-P2 - A'yunin, Qurratin; Rochayatun, Sulis (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
A quantitative study seeks to test and determine the partial and simultaneous effects of tax knowledge, tax socialisation, tax incentives, and trust in tax authorities on the level of tax payment compliance (PBB-P2) in Mojokerto district as seen from the amount of receivables each year always increases, indicating that tax compliance behavior is not yet optimal. The results of this study can contribute to the Mojokerto Regency government as a reference in tax compliance issues that can support a decrease in tax receivables. Primary data collection was conducted through the distribution of questionnaires, which were conducted online using Google Form and offline, which were complemented by secondary data. The research sample totalled 100 PBB-P2 taxpayers, selected using purposive sampling techniques from 18 sub-districts in Mojokerto district. Data analysis was conducted using descriptive statistics, classical assumption testing, multiple linear regression testing, t-test, and F-test assisted by SPSS software version 26. The results showed that partially, tax knowledge, tax incentives, and trust in tax authorities have a positive and significant effect on PBB-P2 payment compliance. However, partially tax socialisation does not show a significant effect. Simultaneously, the four independent variables significantly influence PBB-P2 payment compliance in Mojokerto district with a significant F-statistic value. Future researchers can expand the independent variable on the tax payment compliance variable (PBB-P2) such as adding the variable level of digital literacy.